Implementasi Teknologi Untuk Pengembangan Sumber Daya Manusia pada Korporasi - Kepler Sinaga (Universitas Batanghari Jambi, 2022)
Rapid changes in human technology affect countless businesses, the strength of a company can be measured by the level of technology applied for efficiency, owning